(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2026)
Mice are important pathogen vectors that infect humans and their livestock. They have been described as potential or important carriers for a number of zoonotic pathogens, considered as sources for signiﬁcant human morbidity and mortality. They live in modified habits as well as natural habits like natural reserves. Abokouamekro, a fauna natural reserve is a prominent tourist spot in the country’s political capital which is so anthropized, an investigation into ectoparasite infestation among mice has never been performed. Thus, the aim was to determine the dynamic of ectoparasites infestation in wild mice in this area. Mice sampled by using live-traps baited with smoked fish and carried out from November 2021 to April 2023. Traps placed in evening and visited next day at twilight. Mice were anesthetized and released after determination of sex and age following by ectoparasite collection. 256 mice were trapped of which the majority in villages (63.67 %) with a sex ratio (Male/Female) of 0.94 (124/132). Most captured mice were juveniles, 75.27 % in villages. 288 ectoparasites were counted and collected among which 182 in the forest reserve. Number of mice hosting ectoparasites differs significantly according to the season (OR= 2.66; 95%CI = [1.03-6.87]; P = 0.036). Ectoparasites species belong to four subclasses of two arthropod classes. Constituent Ratio (C) and Prevalence (p) were indices that vary significantly for Xenopsylla cheopis specie (P < 0.0001; P < 0.0001) and for Laelaps echidninus specie (P = 0.0081; P = 0.04468). In Conclusion, different ectoparasite species injure mice with an important risk during dry season and they may be transmitting bacteria and virus to animals and humans. The findings indicate that, although the risk of injury to mice remains high during the dry season, regular monitoring of both mouse health and the health of surrounding populations is necessary. Asian Australas. J. Biosci. Biotechnol. 2026, 11(1), 5-17